The effect of proximity of the landing gear lights on its turbulent wake. Issue 10 (2nd October 2016) - Salt, Eric; Arežina, Marko; Lepore, James; Ziada, Samir
ABSTRACT: A simplified model of a landing gear is tested in a wind tunnel to investigate the effect of the landing light location on the resulting noise generation. Examination of the near-field pressure fluctuations, combined with phase-locked stereoscopic particle imaging velocimetry of the unsteady wake identified two distinct sources of pressure fluctuations. The higher frequency source has a wide frequency band and is situated in the outer regions of the wake near the lights. On the other hand, the lower frequency source is found to be stronger, has a narrower frequency band and is developed further downstream in the wake, closer to the wake centreline. The lower frequency source is observed to be rather robust as it is hardly affected by the location of the landing lights, whereas the higher frequency source becomes weaker as the spacing between the lights is reduced. The effect of a splitter plate positioned downstream of the landing gear strut is also investigated as a means of reducing the lower frequency pressure fluctuations. Although the lower frequency source is considerably weakened by the splitter plate, substantial enhancement of the higher frequency source is observed.